What do we know about the effects of mental training applied to combat sports? A systematic review - Andreato L.V.* (2022)
© 2022 Elsevier LtdObjectives: This study aimed to investigate the effects of mental training applied to combat sports athletes. Methods: A systematic review was conducted, following the criteria recommended by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement, from inception up to February 2021, with an electronic search in PubMed, Scopus, Web of Science, PsycINFO, and SPORTDiscus databases. As eligibility criteria, this review included original studies that carried out any type of mental training, with or without a control group, acute or chronic, in combat sports athletes, of both sexes, age >16 and < 45 years old, from any competitive level, and evaluated the effect of these interventions on psychological measures. The quality assessment was conducted through the application of the Cochrane Collaboration tool. Results: In total, 1921 studies were found and after application of the inclusion and exclusion criteria, 21 articles were included in this review. A total of 417 subjects were investigated from the 21 studies. As results, despite the variations in the type and characteristics of the interventions, studies showed that mental training seems to improve anxiety, mood, self-confidence, emotions, cohesion, emotional balance, and relaxation, in addition to physical and athletic performance. Conclusions: This systematic review based on the evidence from the selected studies indicates that mental training seems to be beneficial for athletes in combat modalities, while combat sports can benefit from mental training in preparation, competition, and recovery. However, the interpretation of these findings must consider that there is limited scientific production with good quality studies investigating the effects of psychological intervention protocols in athletes of combat sports in different combat modalities. Prospero register number: CRD42020169793.